2012
DOI: 10.2527/jas.2011-4721
|View full text |Cite
|
Sign up to set email alerts
|

Changes in protein abundance between tender and tough meat from bovine Longissimus thoracis muscle assessed by isobaric Tag for Relative and Absolute Quantitation (iTRAQ) and 2-dimensional gel electrophoresis analysis1

Abstract: The aim of this study was to find potential biomarkers for meat tenderness in bovine Longissimus thoracis muscle and to compare results from isobaric Tag for Relative and Absolute Quantitation (iTRAQ) and 2-dimensional gel electrophoresis (2-DE) analysis. The experiment included 4 tender and 4 tough samples, based on shear force measurements at 7 d postmortem, from young Norwegian red (NRF) bulls, taken at 1 h postmortem. A number of the proteins which have previously been related to tenderness were found to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
50
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 45 publications
(52 reference statements)
9
50
1
2
Order By: Relevance
“…The finding coincides with the lower pH and higher Note: a, b means within a row with different superscripts are significantly different at P < 0.05 Nota: a, b los promedios en una misma fila con diferente superíndice son significativamente distintos a P < 0,05 tenderness in gas-stunned birds compared with their Halal counterparts. In line with the current finding, increased expression of creatine kinase has been associated with increased meat tenderness in cows (Bjarnadóttir et al, 2012;Zapata, Zerby, & Wick, 2009). Gas stunning up-regulated (P < 0.05) pyruvate kinase isozyme.…”
Section: Muscle Proteomesupporting
confidence: 76%
“…The finding coincides with the lower pH and higher Note: a, b means within a row with different superscripts are significantly different at P < 0.05 Nota: a, b los promedios en una misma fila con diferente superíndice son significativamente distintos a P < 0,05 tenderness in gas-stunned birds compared with their Halal counterparts. In line with the current finding, increased expression of creatine kinase has been associated with increased meat tenderness in cows (Bjarnadóttir et al, 2012;Zapata, Zerby, & Wick, 2009). Gas stunning up-regulated (P < 0.05) pyruvate kinase isozyme.…”
Section: Muscle Proteomesupporting
confidence: 76%
“…For example, the study on porcine LTL exudate proteome [28] identified several enzymes involved in energy metabolism (e.g., phosphoglycerate kinase 1, alphaenolase and malate dehydrogenase, cytoplasmic) whose ovine analogues were also detected in the sarcoplasmic fraction of our study. Also, while both our and the bovine study [82] identified the abundant skeletal muscle proteins such as myosin-1 (myosin heavy chain 1), troponin T, fast skeletal muscle and glucose-6-phosphate isomerase, some proteins were detected only in the bovine study, e.g., cysteine and glycine-rich protein 3.…”
Section: Fig 3 -Number Of Proteins Identified In the Three Crude Framentioning
confidence: 64%
“…Currently, most of them are differential studies aiming to identify only the proteins that exhibit differential abundance, to the best of our knowledge. A few studies focusing on LTL did involve identification of the proteome in their samples, including one for bovine [82] and three for porcine [28,83,84]. They are briefly summarised in Table 1.…”
Section: Fig 3 -Number Of Proteins Identified In the Three Crude Framentioning
confidence: 99%
“…A positive correlation between MLC 1 and shear force has been observed in pork longissimus (Hwang et al, 2005). Furthermore, in beef longissimus thoracis, MLC 1 was of greater abundance in tough meat than in tender meat (Bjarnadottir et al, 2012).…”
Section: Resultsmentioning
confidence: 84%